The BRICS Dilemma: A Polyheuristic Analysis of Indonesia's Free-Active Foreign Policy Shift - Dendy Raditya Atmosuwito; Yunus Ikhsan Bahari; Wibi - Lungidradityo (Institute of International Studies, 2025)
This article examines the complex decision-making process behind Indonesia's pivotal shift to pursue full membership in the BRICS consortium. For decades, Indonesia, a prominent middle power, has navigated global politics through its